A community based cross-sectional study on prevalence and its associated risk factors of geriatric malnutrition in urban and rural Puducherry - Sivapushani Aruljothi; K. Devi; Prakash Mathiyalagen; Sivadamien Thirunavukarasu (Discover Public Health)
Abstract Background The magnitude of geriatric malnutrition is under reported in developing nations. It is essential to assess the nutritional status of the elderly for achieving the better quality of life. Objectives To estimate and compare the prevalence and assess the risk factors that are associated with geriatric malnutrition in the urban and rural field practice areas of tertiary care hospital, Puducherry. Setting and design A community based cross-sectional analytical study done among elderly population in the urban and rural field areas of Government Medical College of Puducherry. Methods Study was conducted among elderly (≥ 60 years) for two years using multistage random sampling technique. Geriatric malnutrition was estimated using Mini Nutritional Assessment (MNA). Sociodemographic data and associated risk factors were obtained using semi-structured questionnaire. Results Prevalence of geriatric malnutrition was 31.3% and 19.3% in rural and urban areas. In the regression analysis, factors such as individuals with higher age group, illiterates, lower socioeconomic status, living without family, presence of two or more co-morbidity, three or more medications intake on daily basis, presence of visual impairment and reduced dietary salt intake because of their health issues were found to statistically significant (p-value < 0.05) both in urban and rural setting. Widower by their marital status was found to have statistically significant association among urban elderly whereas those who had dental problems, financially dependency was independently associated with malnutrition among the rural elderly. Conclusions There was a high prevalence of malnutrition among elderly residing in rural area than in urban area.